The Cultures of Work OrganizationsThe Cultures of Work Organizations, by TriceHarrison M. and BeyerJanice M.. Englewood Cliffs, NJ: Prentice Hall, 1993. - McCollom, Marion (Academy of Management Review, 1994)
The article reviews the book ?The Culture of Work Organizations,? by Harrison M. Trice and Janice M. Beyer.